2008
DOI: 10.1002/dev.20297
|View full text |Cite
|
Sign up to set email alerts
|

No stable arm preference during the pre‐reaching period: A comparison of right and left hand kinematics with and without a toy present

Abstract: Adult hand preference emerges from complex developmental changes in arm and hand use during childhood. Recent reports have highlighted the importance of understanding arm and hand use during the first year of life including the period before reach onset. This longitudinal study tested the hypothesis that significant right-left differences exist in pre-reaching arm movements. We examined right and left hand kinematics from 13 healthy infants during trials with and without a toy present from 8 weeks of age throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 70 publications
(91 reference statements)
1
22
1
1
Order By: Relevance
“…At 5 months of age infants reach equally with the right and left when a toy is presented at midline (Souza, de Azevedo Neto, Tudella, & Teixeira, 2012). From ages 6 to 12 months infants show unstable hand-use preference, meaning they do not show a consistent side of the body for reaching (Ferre, Babik, & Michel, 2010;Lynch, Lee, Bhat, & Galloway, 2008). As such, early stable hand preferences may signal a motor disability.…”
mentioning
confidence: 94%
“…At 5 months of age infants reach equally with the right and left when a toy is presented at midline (Souza, de Azevedo Neto, Tudella, & Teixeira, 2012). From ages 6 to 12 months infants show unstable hand-use preference, meaning they do not show a consistent side of the body for reaching (Ferre, Babik, & Michel, 2010;Lynch, Lee, Bhat, & Galloway, 2008). As such, early stable hand preferences may signal a motor disability.…”
mentioning
confidence: 94%
“…Kinematic analyses of these steps show quite clearly that significant changes occur over these 12 mo in infants' leg movement patterns and interlimb coordination (Groenen et al 2010;Thelen and Ulrich 1991;Vereijken and Thelen 1997), as is true of all other motor behaviors when assessed over such a wide developmental time frame in infancy (e.g., Adolph et al 1998;Freedland and Bertenthal 1994;Haehl et al 2000;Konczak and Dichgans 1997;Lynch et al 2008).…”
mentioning
confidence: 99%
“…As observed previously by the age of voluntary reaching onset (Lynch et al, 2008;Morange & Bloch, 1996;Ramsay, 1980;Rönnqvist & Domellöf, 2006;Seth, 1973;Souza et al, 2012), infants' handedness was found to be quite variable regarding both the selection of the right or the left hand and the consistency of that choice. Approximately half the infants showed either undefined or left hand preference.…”
Section: Discussionmentioning
confidence: 53%
“…That perceptual lateral bias has been proposed to be a potential factor inducing the predominant preference for the right hand to perform motor tasks in humans (Coryell & Michel, 1978;Michel, 1981;Michel & Harkins, 1986). Even though predominant side of head turning in the first months of life has been suggested to predict manual preference in older infants (Michel & Harkins, 1986), by the age of voluntary reaching onset manual preference is rather variable (Jacobsohn, Rodrigues, Vasconcelos, Corbetta, & Barreiros, 2014;Lynch, Lee, Bhat, & Galloway, 2008;Morange & Bloch, 1996;Ramsay, 1980;Rönnqvist & Domellöf, 2006;Seth, 1973;Souza, Azevedo Neto, Tudella, & Teixeira, 2012). Morange and Bloch (1996), for example, found predominance of left-handedness in 4-month-old infants, whereas Souza et al (2012) found approximately the same numbers of right-and left-handers in 5-month-olds.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%